EVIDENCE OF MICROPLASTICS IN AGRICULTURAL WATER SYSTEMS OF NINH BINH PROVINCE, NORTHERN VIETNAM - Thi Thanh Nga, Cao; Thi Phuong Quynh, Le; Thi My, Nguyen; Thi Thuy, Duong (HNUE Journal of Science: Journal of Natural Sciences, 2024)
Microplastics are regarded as an emerging threat to water and other environments. The increasing use of plastics in agricultural cultivation has led to higher risks and more dangerous pollution of agricultural water. However, microplastics in agricultural water in Vietnam have neither been studied nor documented in any publication. To provide initial scientific evidence of microplastics in agricultural water in the country, we conducted a case study in Kim Son district, Ninh Binh province. Water samples were randomly collected from 15 representative sites within the canal systems of the study area. Our study results indicated that the agricultural water in the study area was polluted by microplastics, which vary considerably in all size, shape, and color aspects. The average concentration of microplastics found in the examined water was 491 ± 259 particles/m³, with detected microplastic sizes ranging from 302 to 4,593 μm. Among these, microplastics sized between 300 and 1,000 μm were the most dominant, accounting for 61.8% of the total detected microplastics. In terms of shape, 94.5% of the detected microplastics were fibers, present at all 15 study sites, while only 5.5% were fragments, found at just seven sites. The microplastics were also highly diverse in color, with white being the most common and densely present in every analyzed water sample. The results of the present study provide the first scientific evidence of microplastic occurrence in agricultural water within the study area and can serve as a crucial basis for comprehensive research and effective management of plastic products in the future.